Effect of seasonal distribution and rate of nitrogen fertilisation on canola production and soil bacterial communities in the Western Cape - Becker, Frederick (Stellenbosch : Stellenbosch University, 2017)
Thesis(MScAgric)--Stellenbosch University, 2017.